Synthesis, characterization and performance of visible light active copper-loaded bismuth vanadate photocatalyst - Wan, Tze Peng (2016)
The intense rise of wastes production in the industrial field due to rapid industrialization had brought more concern and interest in the development of wastewater treatment technologies in the country. The aim of this study is to synthesize simple, high efficiency and environment-friendly photocatalyst with easy and affordable photodegradation experiments in degrading dye. In this study, a series of bismuth(III) vanadate (BiVO4) photocatalysts were prepared via precipitation method and a series of Cu-loaded BiVO4 (Cu-BiVO4) photocatalysts were prepared via impregnation method. XRD analysis showed that tetragonal phase of BiVO4 was formed during precipitation process and the phase transformation from tetragonal to monoclinic phase of BiVO4 was completed at temperature 450 °C after 4 hours of calcination in air. The crystallite size of the synthesized photocatalysts ranging from 25.8 to 51.1 nm. The synthesized photocatalysts were spherical in shape, as observed in FESEM images, with surface area from 0.2 to 0.8 m2g-1. The particle size of the photocatalysts obtained via TEM, was in the range of 34.1 to 60.6 nm. Result from UV/Vis DRS indicated that band gap energy of BiVO4 had increased due to copper loading. The presence of copper in the Cu-BiVO4 photocatalysts was justified by result of AAS. Photocatalytic degradation efficiency of the BiVO4 and Cu-BiVO4 photocatalysts was evaluated by degrading methylene blue (MB) dye under visible-light irradiation. The optimum conditions of the photocatalytic degradation were based on parameters. Among the undoped BiVO4 photocatalyst, sample calcined at 550 °C for 1 hour demonstrated the highest photocatalytic degradation efficiency. Highest removal percentage of MB dye solution at initial concentration of 10 ppm and initial pH at 8, was achieved by loading 1.0 g of BiVO4 in the photocatalytic degradation experiment, under 18W fluorescent light irradiation at room temperature. The photocatalytic degradation efficiency of BiVO4 photocatalyst was enhanced by doping copper (Cu). 1 wt% Cu-BiVO4 was found to exhibit the highest photocatalytic degradation efficiency. The percentage removal of MB dye solution at initial concentration of 10 ppm and initial pH at 10, approached 99.57%, when 0.8 g of 1 wt% Cu-BiVO4 was loaded in the photocatalytic degradation experiment, under 18W fluorescent light irradiation at room temperature. The photocatalytic degradation of MB dye in this study followed first order kinetics.